Resolvin D1 Attenuates Doxorubicin-Induced Cardiotoxicity by Inhibiting Inflammation, Oxidative and Endoplasmic Reticulum Stress - Wang, Menglong; Zhang, Jishou; Zhao, Mengmeng; Liu, Jianfang; Ye, Jing; Xu, Yao; Wang, Zhen; Ye, Di; Li, Dan; Wan, Jun (Frontiers in Pharmacology, 2022)
Resolvin D1 (RvD1) is a lipid mediator that promotes resolution of inflammation. However, the function of RvD1 in doxorubicin- (Dox-) induced cardiotoxicity remains to be clarified. This study aimed to investigate whether RvD1 could attenuate Dox-induced cardiac injury. The mice were divided into three groups: control, Dox (20mg/kg, once, intraperitoneally), and Dox + RvD1. RvD1 (2.5 μg/kg, intraperitoneally) was injected daily for five days. Echocardiography was performed to evaluate the cardiac function, and the heart tissue and serum samples were collected for further analyses. The results showed that RvD1 attenuated the decreased ratio of heart weight/body weight and heart weight/ tibia length, the increased level of creatine kinase and activity of lactate dehydrogenase after Dox treatment. RvD1 improved the ejection fraction and fractional shortening of left ventricular and attenuated the severity of apoptosis induced by Dox. As for the underlying pathways, the results showed that RvD1 reduced the expression of IL-1 and IL-6, and attenuated the phosphorylation of P65 in cardiac tissue. RvD1 attenuated the oxidative stress induced by Dox, as demonstrated by the attenuated levels of superoxide dismutase, glutathione, and malondialdehyde, decreased expression of Nox-2 and Nox-4 and increased expression of Nrf-2 and HO-1. In addition, RvD1 also inhibited the endoplasmic reticulum stress induced by Dox. These results indicate the potential therapeutic benefits of RvD1 in Dox-induced cardiotoxicity in mice, and the mechanism may be related to the attenuated inflammation, oxidative stress and endoplasmic reticulum stress.